Early childhood poverty and adult executive functioning: Distinct, mediating pathways for different domains of executive functioning. Issue 5 (15th February 2021) - Evans, Gary W.; Farah, Martha J.; Hackman, Daniel A.
Abstract: Executive functioning in adulthood is associated with early‐in‐life disadvantage. Furthermore, distinct and independent underlying processes account for differences in specific domains of adult executive functioning. The duration of poverty from birth to age 9 is associated with reduced adult inhibitory control assessed by the Flanker task ( n  = 233, M = 23.52 years). This effect is largely explained by lower levels of maternal responsiveness in adolescence. Early poverty also related to worse working memory in adulthood, and this effect is partially explained by elevated allostatic load during adolescence, an index of chronic physiological stress. Abstract : Distinct mediating pathways are shown between childhood poverty and different domains of adult executive functioning.